2007
DOI: 10.1373/clinchem.2006.083675
|View full text |Cite
|
Sign up to set email alerts
|

SPP1 Promoter Polymorphisms: Identification of the First Modifier Gene for Pseudoxanthoma Elasticum

Abstract: Background: Progressive calcification and fragmentation of elastic fibers are characteristic hallmarks of pseudoxanthoma elasticum (PXE), which is caused by mutations in ABCC6 encoding multidrug resistanceassociated protein 6 (MRP6). Because of the great clinical variability of PXE, secondary genetic risk factors are suspected to exist. We investigated whether SPP1 (secreted phosphoprotein 1; previously OPN, osteopontin) promoter polymorphisms are associated with PXE. Methods: We screened an ϳ2-kb region spann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…The G base insertion at À156 site of OPN promoter generates another Runx2-binding site, 19,22 and Runx2 bindings are crucial for regulation of OPN transcription in bone tissue. 36 As discussed above, enhanced expression of OPN in heart potentially causes cardiac dysfunction.…”
Section: Renin-angiotensin System and Opn Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The G base insertion at À156 site of OPN promoter generates another Runx2-binding site, 19,22 and Runx2 bindings are crucial for regulation of OPN transcription in bone tissue. 36 As discussed above, enhanced expression of OPN in heart potentially causes cardiac dysfunction.…”
Section: Renin-angiotensin System and Opn Expressionmentioning
confidence: 99%
“…17,18 Recently, three functional polymorphisms (À66T/G, À156del/G and À443T/C) on the promoter region of OPN gene have been found to affect gene expression by altering transcriptional activity 19 and reported to be associated with several diseases, including pseudoxanthoma elasticum, stroke and chronic hepatitis C. [20][21][22] The insertion of guanine base at position À156 (À156G allele) on the OPN promoter generates a Runx2 binding site so that the binding of Runx2 factor to the À156G position promotes OPN transcription. 19 In the present study, we investigated the association between diastolic dysfunction and the À156del/G polymorphism on the OPN promoter in patients with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, promoter polymorphisms of the SPP1 gene were significantly more often present in patients with PXE than in controls, so that it was suggested that SPP1 is a modifier gene for PXE. 29 Furthermore, a correlation was reported between polymorphisms in three genes encoding for antioxidant enzymes (CAT, SOD2, and GPX1) and age of onset of PXE. 30 Higher serum concentrations of the calcification inhibitor matrix Gla protein (MGP) were correlated with later onset of PXE.…”
Section: Phenotype In the Patients With Pxementioning
confidence: 99%
“…The allele and genotype frequencies differed from those previously reported in Caucasians. 20 The allele frequencies of the À443C/T SNP for SPP1T were 0.654 in controls and 0.672 in patients. The genotype frequencies of this site for CC, CT and TT in cases and controls were 0.103, 0.448, 0.448 and 0.115, 0.463, 0.423, respectively ( Table 2).…”
Section: Characteristics Of the Study Populationmentioning
confidence: 94%